Edukasi Gizi sebagai Upaya Atasi Permasalahan Stunting di Desa Cikahuripan, Kabupaten Sukabumi - Oktaviani, Rahmadiyanti; Manurung, Rinto Aditya; Azizah, Faiza Tsaniya Nur; Harjanti, Anisa Tri; Puspita, Sylva; Suyatman, Diki; Syaputra, Muhammad Wahyu Raka; Baskoro, Nadin Aulia; Meilani, Resti (Jurnal Pusat Inovasi Masyarakat, 2024)
Stunting is a serious health problem in Indonesia that can occur due to chronic malnutrition, infections, low parental education, low household socio-economic levels, and other factors. Cikahuripan Village, Cisolok District, Sukabumi Regency, West Java, is one of the stunting loci, with 24 toddlers recorded as experiencing stunting. One of the challenges in preventing stunting in rural areas is the limited access to health information. Nutrition education interventions are needed to increase knowledge about stunting. The Gemilang program aims to increase public understanding of stunting prevention through weaning food and to distribute Supplementary Food for stunted children and pregnant women with Chronic Energy Deficiency (CED). This program is implemented through education, weaning food cooking demonstrations and supplementary food making. The evaluation was conducted using pre-test and post-test and analyzed with a paired t-test statistical test and N-Gain calculation. The results showed a significant increase (p<0.05) in participants' knowledge, with an average pre-test score of 48.82%, an average post-test score of 85.29%, and an N-gain value of 0.69. The result is is interpreted as a moderate increase in knowledge, showing that the activity was quite effective in increasing participant knowledge. Improvement efforts related to the provision of materials and participant participation are still needed to strengthen the health education program. Further research and evaluation can be conducted to assess sustainable programs' impact on stunting reduction rates in Cikahuripan Village.